2012
DOI: 10.4161/onci.21056
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MHC Class I on breast cancer cells correlates inversely with HER2 expression

Abstract: HER2 is a promising target for immunotherapeutic interventions with T cell-based approaches since it is amplified and overexpressed in 20–30% of breast cancers. However, several previous studies including ours showed that HER2-overexpressing tumors may escape cytotoxic T lymphocyte-mediated lysis by downregulating MHC Class I and components of the antigen-processing machinery. The aims of the present study were to analyze the relationship between HER2 and MHC Class I expression and to elucidate the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Possible reasons for the difference in results between our study and previous studies could be differences in the cell types and the HER2 sequences targeted by siRNA. [20][21][22] In our study, we found that treatment of the cells with siRNA#1, which knocked down HER2 and increased expression of HLA-ABC, also upregulated expression of STAT1, a known major transcription factor regulating HLA-ABC expression. 27 However, we did not find STAT1 upregulation following treatment with any of the other four siRNAs, suggesting a possible off-target effect of siRNA#1.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Possible reasons for the difference in results between our study and previous studies could be differences in the cell types and the HER2 sequences targeted by siRNA. [20][21][22] In our study, we found that treatment of the cells with siRNA#1, which knocked down HER2 and increased expression of HLA-ABC, also upregulated expression of STAT1, a known major transcription factor regulating HLA-ABC expression. 27 However, we did not find STAT1 upregulation following treatment with any of the other four siRNAs, suggesting a possible off-target effect of siRNA#1.…”
Section: Discussionmentioning
confidence: 72%
“…A few earlier studies showed that HER2 regulates the components of the MHC class I antigen processing machinery and showed that there was an inverse correlation between HER2 and HLA-ABC expression following siRNA-mediated knockdown of HER2 expression in some breast cancer cell lines (SKBR3 and MCF7-HER2) and some non-breast cancer cell lines. [20][21][22]33,34 In our study, we examined the effect of HER2 knockdown in five HER2-overexpressing cell lines using five different siRNAs. We did not find a significant inverse correlation between the levels of expression of HER2 and HLA-ABC except with one particular siRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could be explained by the interference of Her2/neu with T-cell recognition via an inhibition of HLA class I molecules mediated by an activation of the MAPK pathway (40,41). An inverse correlation between Her2/neu and MHC class I antigenprocessing machinery (APM) component levels in human mammary carcinoma lesions has also been reported supporting this hypothesis (41).…”
Section: Discussionmentioning
confidence: 87%
“…45 NeuT C tumor cells are susceptible to the activity of NK cells, as an inverse correlation exists between the expression levels of neuT protein and those of MHC class I molecules as well as other components of the antigen-processing machinery. 46 Moreover, signaling through the Her2/Her3 pathway in breast tumor cell lines has been shown to enhance their recognition by NK and T cells thanks to the killer cell lectin-like receptor subfamily K, member 1 (KLRK1, or NKG2D). 47 In conclusion, our data demonstrate that the C1q protein protects against the development of Her2/neu C mammary carcinomas, at least in our preclinical BALB-neuT female mouse model.…”
Section: Discussionmentioning
confidence: 99%